Clinicopathological Predictors of Central Compartment Lymph Node Metastases in cN0 Papillary Thyroid Carcinoma - Purnomo, Henricus SW.; Yulian, Erwin D.; Makes, Benyamin; Wangge, Grace (The New Ropanasuri Journal of Surgery, 2017)
Introduction. Prevalence of the lymph node metastases of central neck compartment in papillary thyroid carcinoma (PTC) and its correlation with regional metastatic remains high. There are pros and cons on central neck dissection which is thought to solve the problem. Selection of appropriate patient to undergo central neck dissection is then essential. Thus, predictive factors were very useful in such selection, and we run a study aimed to find out the clinicopathological predictive factors for metastases of central compartment in subjects treated in Cipto Mangunkusumo General Hospital. Method. Data of 62 cN0 papillary thyroid carcinoma (PTC) subjects who underwent central neck dissection were collected consecutively and retrospectively studied. The correlations between clinicopathological factors such as age. Gender, tumor size, extra thyroid extension. Distant metastasis, completeness of resection, histopathology variant, lymphovascular invasion and central compartment metastases were the variables analyzed. Chi square. Fischer exact and stratification test were used. Significance found if p value of <0.05 with 95% confidence interval. Results. In this study, the prevalencein our hospital is 20.9%. The clinicopathological factors that statistically showed significance were the positive lymphovascular invasion (OR=14.40; p<0.05), tall cell variant (OR= 14.00; p <0.05), positive extra thyroid extension (OR=10.44; p<0.05) and age ≥45 years (OR= 9.47; p <0.05). Lymphovascular invasion showed a higher OR (OR=14.40). Conclusion. The lymphovascular invasion, tall cell variant, extra thyroidal extension and age might be the predictors for central compartment lymph node metastases in cN0 PTC patients. However, lymphovascular invasion has the highest risk factor for central neck compartment metastases.